Current Status of Research on Marine Intelligent Unmanned Equipment Detection Based on Multi-Physics Fields - Yuyang WANG; Fang JI; Shaoqing LU; Guonan LI (水下无人系统学报)
The marine intelligent unmanned equipment represented by unmanned undersea vehicles and unmanned surface vessels have the characteristics of large number, small size, high degree of intelligence, and wide range of tasks. Future naval warfare missions will use lots of marine intelligent unmanned equipment, so the detection technology of marine unmanned intelligent equipment has become one of the key technologies in the armament and scientific research of all countries. This paper provided an overview of the detection methods of marine intelligent unmanned equipment in recent years in various countries, covering the optical, electric, magnetic, and other information sources of new types of physical fields. The feasibility of multi-system collaborative detection and multi-information omnidirectional sensing techniques was analyzed, while the current research status of deep intelligent algorithm-based line-spectrum feature detection was described. In the future, the detection of marine intelligent unmanned equipment will develop towards intelligence, clustering, high precision, robustness, and timeliness, and further improving the level of underwater target recognition will be an important research direction.